An Actinomycetes Producing Anticandida Isolated from Cajuput Rhizosphere: Partial Identification of Isolates and Amplification of pks-I genes - A. Alimuddin; Widya Asmara; Jaka Widada; M. Mustofa; Reni Nurjasmi (Indonesian Journal of Biotechnology, 2010)
Actinomycetes have been the most prolific producer of various kinds of antifungal metabolites, and many of them are described as being produced by polyketide synthetases (pks). We present strain of Actinomycetes producing anticandida isolated from rhizosphere plant for amplification of Pks-I genes. The isolate was obtained from Wanagama I Forest UGM Yogyakarta. Gene of seven isolates, from total of 173 isolates, were amplified using degenerate primer to detect the presence of pks genes. One strain that is named Streptomyces sp. GMR-22 was partialy identified as anticandida producing actinomycete. The strain shown the strongest activity against Candida albicans. Based on bioautography assay, one spot active with Rf 0.57 was appeared as bright yellow by cerrium sulphate but it was and not visible on UV254 and 366 lights. Key words : pks genes, anticandida, Streptomyces sp GMR-22, rep-PCR, cajuput rhizosphere